PENYULUHAN DAN PENGENALAN BAHAYA NARKOBA SEBAGAIBENTUK PENCEGAHAN DINI PENGGUNAAN NARKOBA PADA ANAK - Anang Hermawan (UII, 2013)
Drug use in the service program is intended as a first step in the prevention ofdrug trafficking among teenagers early on. Elementary school students grades 5 and 6are students with the transition to the age of adolescence for the next 1-2 years theywill move into the adolescent level. When children move on to middle and high schooleducation usually desire to explore for themselves become more powerful, and tend tobe dangerous and are vulnerable to the negative things.Lack of knowledge of the greatdangers that lurk as a result of their delinquency makes the juvenile may be falling preyto trafficking and drug use. Moreover, based on author interviews with the schoolobtained the explanation that the introduction of drug activities or similar activitiesrelated to the prevention of juvenile delinquency had not been established at all.In thatregard the authors deliberately do this activity as a form of devotion in order to reducenegative behavior and drug abuse and other harmful additives in the future. In theactivities carried out for approximately 12 hours these children are very enthusiastic andbe understood definitions, forms, uses and dangers of drugs and commit to not use it inthe future.